JANUBIY O‘ZBEKISTON SUV HAVZALARI ZULUKLARINI O‘RGANISHGA OID ILK MA’LUMOTLAR - Usmonov , S.X.; Solijonov, X.X.; Izzatullayev , x.I.; Izzatullayev , Z.I (Actual problems and prospects of the study of the fauna, 2024)
This article examines the history of research and species composition of leeches (Hirudinida) found in the aquatic environments of Southern Uzbekistan. Based on the analysis of relevant scientific literature, the study highlights the biological and ecological characteristics of leeches, their role in aquatic ecosystems, and their distribution areas. Additionally, the scope and results of existing studies are analyzed, emphasizing that the leech fauna of Southern Uzbekistan has not yet been sufficiently studied.